2008
DOI: 10.1111/j.1440-1819.2008.01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of subjective and objective quality of life in outpatients with schizophrenia

Abstract: Cognitive dysfunction had a greater influence on objective QOL than subjective QOL. Treating depressive and negative symptoms and extrapyramidal symptoms might contribute to enhanced subjective and objective QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
60
2
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 42 publications
7
60
2
4
Order By: Relevance
“…In the study, stepwise regression analyses when using several clinical variables including the BACS scores as independent variables showed that the QLS total score was significantly predicted by the PANSS negative syndrome scale score, the CDSS score, and the BACS Attention and speed of information processing score. The results were rather consistent with those of previous researches in terms of that cognitive dysfunction was on the whole related to lowered objective QOL (28,30,37).…”
Section: Relation Between Cognitive Func-tion and Quality Of Lifesupporting
confidence: 91%
See 1 more Smart Citation
“…In the study, stepwise regression analyses when using several clinical variables including the BACS scores as independent variables showed that the QLS total score was significantly predicted by the PANSS negative syndrome scale score, the CDSS score, and the BACS Attention and speed of information processing score. The results were rather consistent with those of previous researches in terms of that cognitive dysfunction was on the whole related to lowered objective QOL (28,30,37).…”
Section: Relation Between Cognitive Func-tion and Quality Of Lifesupporting
confidence: 91%
“…To elucidate the relation between cognitive function and QOL in schizophrenia patients, Yamauchi et al (37) investigated the relations between the SQLS, the QLS, and the PANSS cognitive factor in 84 outpatients with schizophrenia. The results showed that although the PANSS cognitive factor was significantly correlated with both of the SQLS and the QLS, it seemed to have a greater influence on the QLS score than the SQLS score.…”
Section: Relation Between Cognitive Func-tion and Quality Of Lifementioning
confidence: 99%
“…This is consistent with previous studies (Yamauchi et al, 2008). These symptoms are more important than positive symptoms in explaining patients' quality of life during the maintenance treatment of schizophrenia.…”
supporting
confidence: 93%
“…(Yamauchi et al, 2008) Objective measures can be observed and recorded by various testing procedures and assessors. Whereas, subjective indicators measure life satisfaction in general and within different life domains.…”
Section: Objective Versus Subjective Measuresmentioning
confidence: 99%
“…Subjective measures provide opportunities for individuals to express their thoughts, knowledge, attitudes, moods, and feelings. (Yamauchi et al, 2008, Medicine&Technology, 1989 …”
Section: Objective Versus Subjective Measuresmentioning
confidence: 99%